PENDEKATAN TARI KREATIF 01 SEKOLAH: SUATU TINJAUAN PROSES PEMBELAJARAN TARI SEBAGAI PEMERKARSA PEMANTAPAN JATI DIRI PELAJAR - Muhammad Fazli Taib Bin Saearani (Institut Seni Indonesia Surakarta, 2011)
Creative dance approach for student who are involved in the creative dance activities can give the appearance of happiness besides the unique potential of most creative dance while enhance their self-esteem. This writing proposed creative dance activity should be develop in our education system in both the academic module and eo-curriculum activities to generate creative minds, colourful imagination and induce students dynamic intellectual capabilities.Key words: teaching creative dance, curriculum, self-esteem